2016
DOI: 10.1007/s10561-016-9568-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing amniotic membrane tissue banking protocols for ophthalmic use

Abstract: Amniotic membrane (AM) due to its anti-inflammatory, anti-scarring and anti-angiogenic properties is used as corneal and wound grafts. When developing AM tissue banks, cell viability, membrane morphology and genomic stability should be preserved following cryopreservation. To analyze the changes rendered to the AM during the process of cryopreservation by comparing different combinations of standard cryopreservation media; fetal bovine serum (FBS), dimethyl sulfoxide (DMSO), Dulbecco's modified eagle's medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…In contrast, Fénelon et al [2018], comparing the impact of preservation methods on AM properties for tissue engineering applications, showed that the epithelial cells presented a slight degree of vacuolar degeneration. Moreover, Hettiarachchi et al [2016] compared the morphology of fresh and cryopreserved AM, demonstrating that AM storage in 1:1 DMEN:glycerol at −80°C disrupted the stromal matrix and the epithelial cell monolayer, presenting patchy areas of epithelial cell loss. The different histological aspects between these 2 works and our study could be due to the cryopreservation media used by Fénelon et al [2018] (e.g., RPIM) and to the longer storage period used by Hettiarachchi et al [2016].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In contrast, Fénelon et al [2018], comparing the impact of preservation methods on AM properties for tissue engineering applications, showed that the epithelial cells presented a slight degree of vacuolar degeneration. Moreover, Hettiarachchi et al [2016] compared the morphology of fresh and cryopreserved AM, demonstrating that AM storage in 1:1 DMEN:glycerol at −80°C disrupted the stromal matrix and the epithelial cell monolayer, presenting patchy areas of epithelial cell loss. The different histological aspects between these 2 works and our study could be due to the cryopreservation media used by Fénelon et al [2018] (e.g., RPIM) and to the longer storage period used by Hettiarachchi et al [2016].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The release of proteins from dead cells in the protein extracts may have contributed to the diminished efficacy for CSK propagation compared to fresh amnion extracts. Alternative cryopreservation in the presence of dimethylsulfoxide (DMSO), a common cryoprotectant to prevent intracellular ice formation, or under freezedrying with the removal of ice through sublimation, can maintain cell viability [48,49]. However, our earlier report has revealed a significant loss of growth factors and ECM proteins (such as laminin and fibronectin) in freeze-dried amnion, which might produce the protein extract with reduced potential in supporting cell growth [50].…”
Section: Discussionmentioning
confidence: 99%
“…Corneal transplantation is relatively rare in comparison to amniotic membrane transplantation, which was confirmed by the current single-center study (7). Corneal transplantation restores visual function, especially when the ocular surface is significantly affected, but depends very much on the retrospective consequences and restauration of the normal anatomical relationships between lids, cornea, and conjunctiva (8,9).…”
Section: Discussionmentioning
confidence: 52%